Value co-creation through APIs in Multi-sided platforms : A design science research in the E-Mobility industry - Meingassner, Markus (My University, 2020)
This thesis discusses various elements of value co-creation through APIs in the context of Multi-sided platforms. A design science research methodology is applied to answer the main research question of how APIs contribute to value co-creation in a Multi-sided platform environment. During the research, a model is developed that shows the impact of offering APIs to complementors, competitors and individual developers. This model is applied in the context of the E-Mobility industry. The target company, a Multi-sided platform provider that connects EV drivers with charging stations, serves as a real-world context for this thesis. During the application of the model, several artifacts are created, and the theoretical model is refined through direct feedback from business and IT professionals in the E-Mobility field.
Keywords: Platform economy, Multi-sided platform, boundary resources, API, value co-creation, API economy, API governance, API management, EV charging, interfaces, E-Mobility